Surface organometallic chemistry in heterogeneous catalysis - Samantaray, Manoja K; Pump, Eva; Bendjeriou-Sedjerari, Anissa; D'Elia, Valerio; Pelletier, Jérémie D. A; Guidotti, Matteo; Psaro, Rinaldo; Basset, Jean-Marie (Chemical Society reviews, 2018)
The broad challenges of energy and environment have become a main focus of research efforts to develop more active and selective catalytic systems for key chemical transformations. Surface organometallic chemistry (SOMC) is an established concept, associated with specific tools, for the design, preparation and characterization of well-defined single-site catalysts. The objective is to enter a catalytic cycle through a presumed catalytic intermediate prepared from organometallic or coordination compounds to generate well defined surface organometallic fragments (SOMFs) or surface coordination fragments (SCFs). These notions are the basis of the "catalysis by design" strategy ("structure-activity" relationship) in which a better understanding of the mechanistic aspects of the catalytic process led to the improvement of catalyst performances. In this review the application of SOMC strategy for the design and preparation of catalysts for industrially relevant processes that are crucial to the energy and environment is discussed. In particular, the focus will be on the conversion of energy-related feedstocks, such as methane and higher alkanes that are primary products of the oil and gas industry, and of their product of combustion, CO 2 , whose efficient capture and conversion is currently indicated as a top priority for the environment. Among the main topics related to energy and environment, catalytic oxidation is also considered as a key subject of this review. Surface organometallic chemistry has been reviewed with a special focus on environmentally relevant transformations (C-H activation, CO 2 conversion, oxidation).